Research on the dismantling of double-arch tunnel after long-term service—the case study of Huangmeishan Tunnel demolition project - Kou, Xinyu; Li, Xiaojun; Xie, Jiangning; Rusuli, Adili; Li, Tao; Rui, Yi (Frontiers in Earth Science, 2023)
Mountain tunnel structures are subject to a variety of diseases with increasing service life. Earlier tunnels may need to be demolished and expanded because of the poor serving capacity. But few studies of tunnel demolition projects are available. Based on the demolition project of Huangmeishan Tunnel, this paper discusses the demolition scheme of the double-arch tunnel, calculates the stability of the slope, and investigates the defects and material performance in the tunnel. The water leakage in the tunnel mainly occurred at the mid-partition wall and the drainage pipe was clogged severely. The largest width of the crack detected is 15 mm. Material performance tests indicated that the concrete material strength exceeded the design values. In the loading test, the largest displacements of the tunnel arch and haunch were 1.73 and 1.32 mm, which verified the safety of heavy vehicles in construction. Finally, suggestions are given to avoid similar phenomena in other tunnels during the design, construction, and operation phase. The novelty of this study lies in its comprehensive analysis of a tunnel demolition project. The findings of this study contribute to enhancing the knowledge and understanding of tunnel demolition and support the safe and efficient execution of future demolition projects.